The insider's guide to graduate degrees in creative writing - Abramson, Seth, 1976- (Bloomsbury Academic, 2018)
"There are so many different creative writing degrees out there! How do I find the right school for me? Bringing together data on creative writing schools and interviews with MFA applicants, creative writing students and faculty, this is a complete practical guide to choosing a creative writing school and putting together a successful application. The Insider's Guide to Graduate Degrees in Creative Writing answers frequently asked questions on such topics as: Creative writing curricula, Student demographics, Acceptance rates, Cost of living, Funding, Postgraduate job placements. The book also includes comprehensive and up-to-date data on creative writing programs available throughout the US, UK and internationally, making this an essential read for anyone planning to pursue a creative writing degree."--